Design And Build A Room Security System Based On Internet Of Things (IOT) - Juman Kundang K; Tjahjono B; Yulhendri; Apresia Kadek (International Journal of Science, Technology & Management, 2021)
Workspace or home security systems required special attention, especially in the issue of locks for room security that must be unique, not easily opened by unauthorized people to enter the room. In this research, indoor security systems applied Internet of things (IoT), the use of MQTT Broker which functions as a getway for data transactions between publishers and subscribers, power supply and ESP8266. The method to building the smart doorlock was use prototype method, designed the system and design diagrams, used UML (Unified Manipulation Language), the analysing problem used the PIECES method. The use of the MQTT broker functions as a gateway to connect publishers, subscribers, power supplies and the ESP8266 wifi module which functions as a gateway between devices to the mobile. The result of this researched was prototype the smart door lock system using IoT.